Relationship Between Lower Limb Muscle Strength and Kyphosis Degree With Fall Risk in Elderly Women: a Cross-Sectional Study - Komang Anna Yuki Adnyaswari; Govinda Vittala; Anak Agung Gede Angga Puspa Negara; Ni Luh Nopi Andayani (Universitas Pahlawan Tuanku Tambusai, 2026)
The growing number of elderly individuals in Indonesia has led to an increased prevalence of physical function impairments, including reduced lower limb muscle strength and postural changes such as kyphosis, both of which are fall risk factors in elderly women. An analytical observational study with a cross-sectional design was conducted on 60 elderly women (≥60 years) selected by purposive sampling from a population of 423 individuals. Lower limb muscle strength was measured using the Back and Leg Dynamometer, kyphosis degree using a flexicurve ruler, and fall risk using the Modified Indonesian Fall Risk Assessment Tool (M-IFRAT). Analysis was performed using Spearman correlation test. The mean respondent age was 67.63 years. The majority had very poor muscle strength (90.0%), 76.7% had normal posture, and 56.7% were classified as high fall risk. There was a significant relationship between lower limb muscle strength and fall risk (r = −0.618; p < 0.001) and between kyphosis degree and fall risk (r = 0.553; p < 0.001). Regression analysis showed that both variables together explained 53.4% of fall risk variation (R² = 0.534). Higher lower limb muscle strength is associated with lower fall risk, while higher kyphosis degree is associated with greater fall risk. Physiotherapy interventions targeting lower limb muscle strengthening and postural correction are recommended as fall prevention strategies for elderly women.